PENGGUNAAN BUKU TEKS MATEMATIKA: STUDI KASUS MAHASISWA PENDIDIKAN MATEMATIKA UNIVERSITAS KUNINGAN - Mohamad Riyadi; Nunu Nurhayati; Nuranita Adiastuty; Heru Haerul Anwar (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2017)
AbstactÂ Textbooks have an important role in the learning process. In addition as a reference material, also have the potential to affect student learning. In this study, carried out a survey of mathematics education students. Students were asked to describe how they used textbooks. The survey was conducted by giving questionnaires and interviews about what components are used, when students look at each component, the reason for these components as well as the students see what difficulties encountered when used textbook. Data collected was processed using descriptive statistics as well as to determine there are differences in the use of good text books for each component or components in pairs using Cochranâ€™s Q test and McNemar Test. The result show that students tend to use the sample chapter to build their understanding of math concept than the chapter text description. Difficulties experienced when students understand basic concepts such as definitions and theorems which causes difficulty in working on.